2014
DOI: 10.1007/s10103-014-1556-x
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced osteoblast proliferation is mediated by ROS production

Abstract: Low-level laser therapy (LLLT) is widely used in regenerative medicine and in dental therapy by virtue of its beneficial effects in a plethora of pathological conditions. In this study, the effect of a 980 nm diode laser on pre-osteoblasts proliferation has been evaluated, along with reactive oxygen species (ROS) production. We hypothesized that ROS were a key factor in LLLT-induced pre-osteoblasts proliferation, as it is known that ROS can induce the activation of many biological pathways, leading to cell pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 26 publications
4
57
0
6
Order By: Relevance
“…20 Furthermore, Bouvet-Gerbettaz et al 21 reported that infrared LLLI at 808 nm could not alter murine bone progenitor cell proliferation and differentiation. Migliario et al 18 reported that although pre-osteoblast proliferation was significantly increased after exposure to low or higher energy, cell proliferation was not promoted at 50 J of irradiation. Taken together, these findings indicate that the biological effects of laser irradiation rely on the parameters of the light source, including laser wavelength, output power density, energy density, and pulse structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Furthermore, Bouvet-Gerbettaz et al 21 reported that infrared LLLI at 808 nm could not alter murine bone progenitor cell proliferation and differentiation. Migliario et al 18 reported that although pre-osteoblast proliferation was significantly increased after exposure to low or higher energy, cell proliferation was not promoted at 50 J of irradiation. Taken together, these findings indicate that the biological effects of laser irradiation rely on the parameters of the light source, including laser wavelength, output power density, energy density, and pulse structure.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] The physiological cell activation at low ROS concentrations is mediated by the activation of transcription factors and the promotion of cell proliferation and differentiation. Cells generate low levels of ROS after LLLI, whereas high-energy laser irradiation induces high levels of ROS, 18,25 which may lead to chronic oxidative stress in cells. The oxidative damage can then inhibit cell proliferation and induce apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several molecular targets have been described. LLLT seems to enhance the electron flow through the respiratory chain in the mitochondria, as a result from photon acceptance on cytochrome c oxidase, leading to increased production of reactive oxygen species (ROS) [3]; as a consequence of this redox signaling imbalance, the transcription factors HIF-1α, NRF2 and NF-κB may be activated, leading to a massive genic response [4] directed to inflammation, repair and proliferation [5][6][7]. Also in the mitochondria, LLLT may enhance the membrane potential * Corresponding author: e-mail: viviancury@usp.br, Phone: (55-11) 3061-8480, Fax: (55-11) 3061-7170 Acute lung injury is a condition characterized by exacerbate inflammatory reaction in distal airways and lung dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Adequate laser power can increase the activity of bacteria and cells. However, too much power causes damage to the bacteria and cells (24)(25)(26). Biostimulatory effects of laser are governed by the Arndt-Schulz law of biology, i.e., weak stimuli excite physiological activity, whereas strong stimuli retard it (27).…”
Section: E Faecalis Colonies On Brain Heart Infusion Agar Plates mentioning
confidence: 99%